Tales of health crises: Indonesia’s dynamic narratives and counter-narratives about pandemics - Rahmi Rahmi; Totok Suhardijanto; Herdito Sandi Pratama; Ratna Djumala; Katrin Setio Devi; Aditia Aditia (Cogent Arts & Humanities)
This study explored Indonesia’s diverse narratives and counter-narratives concerning pandemics with a focus on public sentiment and governmental responses. The research highlighted the challenges and complexities of sentiment analysis in such a multifaceted field by gathering data from numerous sources, including the unstructured terrain of Twitter and more regimented online media platforms. The study shed light on the government’s occasional reticence in directly challenging or addressing public views about pandemic regulations. Technical challenges, particularly with tools such as AntConc, further emphasised the need for rigorous digital tools that are tailored to complex datasets. A pronounced difference between narratives on platforms such as Twitter and those on structured online media was observed, thus highlighting the necessity of diverse analytical approaches for different media sources. Despite its thoroughness, the study acknowledges several limitations, including the nuances of Twitter data and the challenges in comparative analysis. This study accentuates the importance of fostering transparent dialogue between policymakers and the public while recognising the evolving nature of narratives in the digital age. Future research is encouraged to refine the methodologies, consider the identified challenges, and develop more nuanced analytical tools for in-depth narrative analyses.